Post-fire succession of small mammals in the Cerrado of central Brazil - Briani, D. C.; Palma, ART; Vieira, E. M.; Henriques, RPB (Springer, 2004)
In the Cerrado savannas from Brazil fire events are common and strongly influence the vegetation structure and, consequently, the associated small mammals. In this paper, we investigate changes in the structure of small mammal communities related to sites of different post-fire ages. Mammals were captured in similar Cerrado sites that differed in time since the last burn ( 1 to 26 yr). We sampled six sites in the wet season of 1997 ( phase 1) and, three years later, six sites in the wet and dry seasons ( phase 2). Six rodent species and four marsupials were captured. Community composition changed drastically as a function of time since fire. The diversity and abundance of small mammals reached maximum values in the early successional stages. The rodent Calomys tener was present only in early seral stages. The rodent Bolomys lasiurus was more frequent in mid-successional stages and decreased in later seral stages, and the rodent Oryzomys subflavus occupied all successional stages. The marsupial Gracilinanus agilis was dominant in the area that did not burn for at least 23 yr. Changes in composition of the community of small mammals were more accelerated in early successional stages, when there are more drastic vegetational changes. The ability of small mammals to cope with Cerrado fires and the great dissimilarity among post-burning seral stages suggest that a mosaic of areas representing different post-fire seral stages could increase the regional diversity of this group.
Keywords: Brazil; Cerrado; fire; marsupials; rodents; small mammals